2010
DOI: 10.3732/ajb.1000258
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of natural Miscanthus (Poaceae) triploid plants in sympatric populations of Miscanthus sacchariflorus and Miscanthus sinensis in southern Japan

Abstract: This is the first report of the natural occurrence of Miscanthus triploid plants in several decades. If found to be sterile and similar in productivity to the commonly cultivated clone of M. ×giganteus, these triploid plants might serve as additional sources of genetic variation for bioenergy production. Seed set data also indicates that other triploid plants might be found in more northern regions of Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 27 publications
1
96
1
Order By: Relevance
“…The DNA content was measured by using FCM (Guava EasyCyte™ 12 HT Flow cytometer). Oryza sativa (1C= 0.5 pg calculated from Bennett and Smith 1976) and Miscanthus sinensis (1C= 2.65 pg calculated from Nishiwaki et al 2011) were used to calculate genome size in absolute units.…”
Section: Flow Cytometry (Fcm) Analysismentioning
confidence: 99%
“…The DNA content was measured by using FCM (Guava EasyCyte™ 12 HT Flow cytometer). Oryza sativa (1C= 0.5 pg calculated from Bennett and Smith 1976) and Miscanthus sinensis (1C= 2.65 pg calculated from Nishiwaki et al 2011) were used to calculate genome size in absolute units.…”
Section: Flow Cytometry (Fcm) Analysismentioning
confidence: 99%
“…The genetic identity of clones obtained mainly via rhizomes translates to high uniformity of morphological, physiological and anatomical characters, which presents a risk for agriculture, hence the imperative to create other sources of plant diversity (Lewandowski et al, 2003). In the last decade, recently established populations of M. ×giganteus that could serve as a new gene source have been found in sympatric populations of its parents in Japan (Nishiwaki et al, 2011). An alternative pathway for obtaining genetic differentiation employs biotechnological methods to modify existing genotypes by transformation or by plant multiplication in vitro via organogenesis or somatic embryogenesis (Lewandowski, 1999;Płażek and Dubert, 2010 and lit.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, the frequency of unreduced gamete production occurs up to 50-fold more often in hybrids between divergent genomes than in non-hybrid systems (Zhang et al 2010). Nishiwaki et al (2011) found that new, naturally derived Miscanthus (Poaceae) triploid genotypes were identified more efficiently by flowcytometry screening of seeds harvested from areas where tetraploid M. sacchariflorus F. plants grow sympatrically with diploid M. sinensis F. plants, than by random identification of triploids in the field. Triploid Arachis pintoi K. (Leguminosae) arose by autopolyploidy as evidenced by FISH and meiotic behaviour (Lavia et al 2011).…”
Section: Natural Selectionmentioning
confidence: 99%